Believing in Tigers: Anthropomorphism and Incredulity in Yann Martel’s Life of Pi - Cole, Stewart (Studies in Canadian Literature, 2004)
Rather than the Bengal tiger with whom he shares a lifeboat for 227 days, Pi Patel’s true adversary in Yann Martel’s Life of Pi is doubt. Pi and his author-narrator align their conception of God with an idea of the work required to believe in narratives that surpass the limits of possibility. Neither Pi nor his author-narrator makes any distinction between the temporary suspension of disbelief and firm religious faith, between the acceptance of a believable story and the embrasure of an omnicient God. By dramatizating the anthropomorphic impulse, which finds expression primarily in response to doubt or disbelief, Life of Pi succeeds in conflating poetic and religious faith.